The effectiveness of an educational game in developing particular professional values, attitudes and acumens - Jogiat, Fathima (College of Accounting, 2024)
The world that we live in is ever-changing at a rapid pace. In order for chartered accountants to remain relevant in our ever-changing world, it is essential that their skills evolve at the same pace. Professional values attitudes and acumens (PVAAs) are crucial skills that must be developed during the journey to becoming a chartered accountant, as required by the South African Institute of Chartered Accountants (SAICA). The purpose of this study is to develop and evaluate the effectiveness of a game that aims to further develop these skills. The game was developed and played by twenty third year Bachelor of Accounting students. A convergent mixed-method research design was applied, to obtain students' perspectives on the PVAAs they applied and developed during the playing of the game. Quantitative and qualitative data was obtained through the use of a survey and the facilitation of focus group interviews. The game was perceived to be effective in creating awareness around the importance of the development of these skills and encouraging application of them. Participants indicated that they enjoyed the game and preferred it over traditional teaching methods. The findings suggest that the game may be effective in further developing these skills in accounting students; thereby providing a practical, engaging teaching option within this challenging area of accounting education.